Rgyud kyi rgyal po brtag pa gñis pa'i tshig 'grel 'jam mgon koṅ sprul gyi gsuṅ = Commentary on the Rgyud brtag gnyis 'Jam mgon kong sprul blo gros mtha' yas - Blo-gros-mthav-yas (Shechen Publ., 2005)
A word to word commentary on the Hevajra Tantra